Comparison of Vascular Closure Devices Versus Manual Compression After Femoral Artery Puncture in Women: Gender-Based Analysis of a Large Scale, Randomized Clinical Trial. (August 2018) - Gewalt, Senta M.; Helde, Sandra M.; Ibrahim, Tareq; Mayer, Katharina; Schmidt, Roland; Bott-Flügel, Lorenz; Hoppe, Katharina; Ott, Ilka; Hieber, Julia; Morath, Tanja; Byrne, Robert A.; Kufner, Sebastian; et al.
Abstract : Background: The value of vascular closure devices (VCD) in women undergoing transfemoral catheterization has not been sufficiently investigated. Methods and Results: This is a sex-specific analysis of 1395 women enrolled in a large-scale, randomized, multicenter trial, in which patients undergoing transfemoral diagnostic coronary angiography were randomly assigned in a 1:1:1 ratio to arteriotomy closure with an intravascular VCD, extravascular VCD, or manual compression (MC). Primary objective was to assess the safety and efficacy of 2 different VCD compared with MC regarding vascular access-site complications at 30 days. A secondary comparison was between 2 different types of contemporary VCD. Overall, women were at higher risk for vascular access-site complications compared with men (9.0% versus 6.4%; P =0.002). Vascular access-site complications were comparable in women assigned to VCD and MC (8.6% versus 9.8%; P =0.451). There was no interaction of treatment effect and sex ( P interaction =0.970). Time to hemostasis was significantly shortened with VCD compared with MC (1 [interquartile range, 0.5–2.0] minutes) versus 11 [interquartile range, 10–15] minutes; P <0.001); however, more women with VCD required repeat MC (2.4% versus 0.6%; P =0.018). The use of the intravascular compared with the extravascular VCD was associated with a numerical reduction in vascular access-site complications (6.6% versus 10.7%; P =0.027) and significant reductions in time to hemostasis and VCD failure. Conclusions: In women undergoing diagnostic coronary angiography via the common femoral artery, VCD and MC provided comparable safety, while time to hemostasis was reduced with VCD. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01389375. Abstract : Supplemental Digital Content is available in the text.